The use of handheld ultrasound devices: a position statement of the European Association of Cardiovascular Imaging (2018 update). (22nd October 2018) - Cardim, Nuno; Dalen, Havard; Voigt, Jens-Uwe; Ionescu, Adrian; Price, Susanna; Neskovic, Alexsandar N; Edvardsen, Thor; Galderisi, Maurizio; Sicari, Rosa; Donal, Erwan; Stefanidis, Alexandros; Delgado, Victoria; et al.
Abstract: Recent technological advances in echocardiography, with progressive miniaturization of ultrasound machines, have led to the development of handheld ultrasound devices (HUD). These devices, no larger than some mobile phones, can be used to perform partial, focused exams as an extension to the physical examination. The European Association of Cardiovascular Imaging (EACVI) acknowledges that the dissemination of appropriate HUD use is inevitable and desirable, because of its potential impact on patient management. However, as a scientific society of cardiac imaging, our role is to provide guidance in order to optimize patient benefit and minimize drawbacks from inappropriate use of this technology. This document provides updated recommendations for the use of HUD, including nomenclature, appropriateness, indications, operators, clinical environments, data management and storage, educational needs, and training of potential users. It also addresses gaps in evidence, controversial issues, and future technological developments.